Implicancia del leasing financiero en la rentabilidad de la empresa Global Rent en el periodo 2011 – 2013 - Piña Ocmín, Jair Neyro (2014)
Globally the construction sector is very important in this area is also shaped by the rental sector of heavy machinery which gives the country a development, and given the different ways of financing the acquisition of machinery is to be determined as the financial leasing influences the economic and financial situation, through its application and analysis on the profitability of the company Global Rent in the period 2011-2013. For which I had to use as a database of financial statements and data declarations of the Superintendencia de Administración Tributaria (SUNAT), with which profitability ratios of the company was determined. Although despite the improvement in profitability for the second year of study, you may notice that this decrease in 2013 due to the costs of repairs of machines. In conclusion it can be noted that the financial leasing positively affect the company as long as operating machinery have within our assets